Self-consistent simulation of high-brightness diode lasers with external optical feedback - Helal, M.A.; Bull, S.; Kaunga-Nyirenda, S.N.; Lim, J.J.; Larkins, E.C. (2015)
This paper presents a model for simulating the impact of external optical feedback on large-optical cavity high-brightness diode lasers. The simulations are performed with our 2.5D simulation tool for high-brightness laser diodes. The external cavity is modelled using commercial coherent ray tracing software. We consider the impact of the optical feedback on the excitation of amplified spontaneous emission in the parasitic vertical modes.